Gendered care work and environmental injustice: A feminist analysis of educator's emotional labor in disaster recovery - Shtob, Daniel A.; Petrucci, Larissa (Environmental Justice, 2021)
Although environmental justice researchers have long been interested in the connections between disaster recovery, gender, and home- and community-based care, the consequences of the post-disaster performance of emotional labor by workers in care occupations have largely gone unnoticed. To address this gap in the environmental injustice literature, in this exploratory article we employ a feminist analysis of firsthand accounts of elementary educators' professional and personal experiences caring for their students in the Florida Keys after Hurricane Irma. We find that caring labor was increasingly necessary in the post-disaster context, both inside and outside the classroom. Teachers and other care professionals in feminized occupations may, therefore, perform an emotional double duty, supporting their students' emotional needs while also contending—as working- and middle-class individuals—with the personal consequences of disaster. We suggest that these educators may bear an unrecognized and undercompensated disproportionate burden at the intersection of class and occupational status. Because of this, we introduce an underexplored component to the racialized disaster patriarchy and intersectional disaster research: feminized occupational status. Inspired by environmental justice research legacies developed in the wake of earlier Gulf Coast disasters, we draw attention to the contributions of these absolutely essential recovery workers and how they may experience environmental injustice even as they contribute to others' recovery. Our goals are to promote recognition and fair distribution of burdens, encourage research into the contours of environmental justice and care work, and support the development of more just planning, training, and compensation regimes.
Keywords: amériques; approches et analyses; care; discipline; floride; intersectionnalité; patriarcat; projet charge mentale; ressource en ligne; régions géographiques; sciences humaines; sociologie; systèmes d'oppressions; thématiques; travail; émotions

Transness as Debility: Rethinking Intersections between Trans and Disabled Embodiments - Baril, Alexandre (Feminist Review, 2015)
Some authors in disability studies have identified limits of both the medical and social models of disability. They have developed an alternative model, which I call the ‘composite model of disability’, to theorise societies’ ableist norms and structures along with the subjective/phenomenological experience of disability. This model maintains that ableist oppression is not the only source of suffering for disabled people: impairment can be as well. From a feminist, queer, trans activist, anti-ableist perspective and using an intersectional, autoethnographic methodology, I apply this composite model of disability to trans identities to consider the potentially ‘debilitating’ aspects of transness. I argue that transness, like disability, has too often been perceived from two perspectives, medical or social, without the benefit of a third option. From a medical perspective, transness is reduced to an individual pathology curable with hormonal/surgical treatments, a conceptualisation that erases structural oppression. From a social point of view, transness is conceptualised as a neutral condition and variation in sex/gender identity. In this model, structural oppression (transphobia/cisgenderism) is seen as the only cause of ‘trans suffering’. I argue that, just as the medical and social models of disability provide limited opportunities for reflection on the complex experience of disability, medical and social understandings of transness, respectively, are insufficient to describe the complexity of trans experience. I explore the possibilities presented by the application of a composite model of disability in trans studies. By both problematising cisgenderist oppression and acknowledging trans people's subjective experiences of suffering through some of the debilitating aspects of transness, this composite model avoids the pitfalls of the medical and social models. The application of tools from disability studies to trans issues uncovers cisnormativity in disability movements and denounces ableism in trans movements. This will, I hope, solidify alliances between these communities and fields of study.
Keywords: LGBTQIA2+; approches et analyses; autoethnographie; care; corps; cours; discipline; identités LGBTQIA2+; intersectionnalité; philosophie; premier cycle; queer; ressource en ligne; santé; santé mentale; sciences humaines; sex1920; sociologie; thématiques; transféminisme; études critiques du handicap; études de genres

Genre, migrations et globalisation de la reproduction sociale - Verschuur, Christine; (Dir), Christine Catarino; Par, Dirigé. (L'Harmattan, 2013)
Les études féministes ont souligné l’importance d’étudier le travail auparavant invisible des femmes, productif et reproductif, et la nouvelle division du travail productif et reproductif dans la mondialisation du capitalisme. L’analyse du capitalisme mondialisé dans une perspective décoloniale permet de comprendre qu’il n’est pas seulement un système économique ni seulement un système culturel mais un réseau global de pouvoir intégré par des processus économiques, politiques et culturels qui constituent un ensemble. Partout on observe un système, social, économique, culturel, moral d’organisation de la reproduction sociale, y compris le care, entendu comme échange économico-affectif, qui implique des biens et des services liés à l’économie capitaliste. Dans le nouvel ordre économique global, que l’on pourrait toujours qualifier de colonial, caractérisé par la nouvelle division internationale du travail, l’articulation entre rapports sociaux dans l’économie domestique et capitaliste prend de nouvelles formes. Mais le système repose toujours sur l’organisation de l’ensemble des activités et des rapports indispensables à la reproduction sociale, par-delà les frontières, dans des réseaux et foyers transnationaux, en s’appuyant sur des discours de genre et de race, voire de classe. Dans ce système, les femmes migrantes sont particulièrement présentes. Elles constituent un maillon essentiel du système de protection sociale aux Nords, y contribuent à la production de richesses, tout en assurant l’organisation de la reproduction sociale aux Suds, dans les foyers qu’elles ont gardés dans leurs pays d’origine.
Keywords: approches et analyses; capitalisme; care; cours; discipline; féminisme décolonial; globalisation; intersectionnalité; justice sociale; militance; pol4022; premier cycle; ressource en ligne; science politique; science politique et droit; sciences humaines; sexualité; sociologie; système colonial; systèmes d'oppressions; thématiques; travail; travail du sexe

Les tactiques féministes confrontées aux « tirs amis » dans le mouvement des femmes en Irlande - Taylor, Judith (Politix, 2007)
Cet article examine les modèles courants d’intelligibilité de l’interaction tactique entre les acteurs des mouvements sociaux et montre leur insuffisance pour rendre compte de l’invention tactique dont a dû faire preuve le mouvement des femmes en Irlande. Une analyse des efforts déployés par les féministes irlandaises pour l’extension du droit à l’avortement met en question l’idée que les innovations tactiques ne répondraient qu’aux contre-mouvements ou à la répression de l’État. L’expression « tir ami » fait référence au processus par lequel des groupes qui ne sont pas en opposition avec un mouvement, mais qui n’en font pas non plus partie, constituent une menace pour les finalités de ce mouvement. L’observation de la campagne féministe, de ses meetings et de l’ensemble de sa mise en scène politique donne des aperçus significatifs sur les effets des tirs amis et, spécifiquement, sur le rôle des hommes dans les mouvements de femmes.
Keywords: 2000 à aujourd'hui; 2000-2009; approches et analyses; avortement; care; corps; cours; discipline; droits des femmes*; europe; intersectionnalité; irlande; justice reproductive; justice sociale; pol5185; premier cycle; périodes historiques; rapports sociaux de sexe; ressource en ligne; régions géographiques; sciences humaines; sociologie; thématiques

Vers une analyse alternative de la mondialisation: les circuits de survie et leurs acteurs - Sassen, Saskia (Cahiers du Genre, 2006)
De nombreuses femmes migrent dans le cadre de la mondialisation : elles partent pour s’occuper du service domestique, garder des d’enfants, devenir infirmières, ou exercer la prostitution; elles utilisent aussi la filière de mariages arrangés. Cette migration est le résultat de conditions ou de dynamiques très diverses dont on peut se demander si elles sont en rupture ou en continuité avec les anciennes histoires bien répertoriées de migration et d’exploitation. Il faut se situer à deux niveaux : d’un côté, les activités souvent traditionnelles, qu’elles soient liées à la survie ou à la recherche de profits, se mondialisent et contribuent aujourd’hui à la création, à l’échelle mondiale, d’une masse de travailleuses mal rémunérées. D’un autre côté, les pays du Nord voient dans l’apport croissant de femmes migrantes un élément leur permettant de réorganiser profondément le monde du travail. Ce genre de dynamique est particulièrement visible dans les villes mondialisées, qui constituent aussi des pôles d’attraction pour le capital multinational. Que ce soit au niveau de la ville ou à celui des circuits de survie, les femmes deviennent des actrices incontournables des nouveaux types d’économie en expansion. On leur attribue une moindre valeur économique et pourtant elles constituent des éléments clés dans la construction des économies nouvelles.
Keywords: 2000 à aujourd'hui; approches et analyses; care; cours; discipline; histoire et politique; intersectionnalité; inégalités; justice sociale; migration; pol4022; premier cycle; périodes historiques; ressource en ligne; science politique; science politique et droit; sciences humaines; sociologie; systèmes d'oppressions; thématiques; travail

Domestic violence at the intersections of race, class, and gender: challenges and contributions to understanding violence against marginalized women in diverse communities - Sokoloff, Natalie J; Dupont, Ida (Violence against women, 2005)
This article provides a comprehensive review of the emerging domestic violence literature using a race, class, gender, sexual orientation intersectional analysis and structural framework fostered by women of color and their allies to understand the experiences and contexts of domestic violence for marginalized women in U.S. society. The first half of the article lays out a series of challenges that an intersectional analysis grounded in a structural framework provides for understanding the role of culture in domestic violence. The second half of the article points to major contributions of such an approach to feminist methods and practices in working with battered women on the margins of society.
Keywords: 2000 à aujourd'hui; 2000-2009; afro-féminisme; amériques; approches et analyses; care; corps; cours; criminologie; discipline; féminisme afroaméricain; intersectionnalité; premier cycle; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; sex2283; sociologie; thématiques; violences; états-unis